Knowledge and Attitudes in Relation to Menstrual Readiness Among Upper-Grade Female Students at SDN Inpres Bertingkat Mabbulo Sibatang, Pinrang Regency - Wijayanati, Siska; Polopadang, Vonny; Taepe, Muh.Yamin; Wijayanti, Eva; Totok, Mega Ayu Lestari (Journal of Midwifery and Nursing, 2025)
Menarche represents a critical stage of biological maturity in girls, which often occurs when they are not yet physically or psychologically prepared. Insufficient knowledge and negative attitudes toward menstruation can lead to fear, anxiety, and misconceptions about reproductive health. This study aims to examine the relationship between the knowledge and attitudes of fifth and sixth grade female students and their readiness to face menarche at SDN Inpres Bertingkat Mabbulo Sibatang, Pinrang Regency. The research employed a quantitative design with a cross-sectional approach. A total of 41 female students who had not yet experienced menstruation were selected through accidental sampling. Data were collected using validated questionnaires and analyzed using the chi-square test. The results revealed a significant relationship between knowledge and readiness for menarche (p = 0.000), as well as between attitude and readiness for menarche (p = 0.000). These findings highlight that students with better knowledge and positive attitudes are more psychologically and behaviorally prepared to experience menarche. The novelty of this study lies in its focus on the early development of menstrual readiness among upper elementary students in a rural public school context, an area that is often overlooked in reproductive health research. This study provides important practical implications for educators, parents, and health workers in strengthening school-based reproductive health education programs. Integrating comprehensive and age-appropriate menstrual education into the elementary school curriculum can promote positive perceptions of menstruation, reduce stigma, and enhance girls’ confidence in managing biological changes healthily and responsibly.